Penyuluhan Penggunaan Antibiotik yang Tepat dan Bijak di Kampung Ciparay Desa Indragiri Kabupaten Bandung : Kegiatan Pengabdian di Tengah Ancaman Resistensi Antibiotik - Fitriyani, Wine; Faidah, Rika Setiani Nur; Maulana, Haris; Fribadi, Lanta; Fauzi, Muhammad Miftah; Syahrir, Annisa Martina (STAI Darul Qalam Tangerang, 2025)
One of the main causes of the increase in antimicrobial resistance cases in the community is the inappropriate use of antibiotics. Community-based educational interventions are needed because people do not understand the indications and procedures for reasonable antibiotic use. In Ciparay Hamlet, Indragiri Village, Bandung Regency, this community service program was implemented with the aim of raising public awareness about the wise and appropriate use of antibiotics. The activity was conducted through lectures and interactive discussions, and 17 participants, mostly housewives, attended. Evaluation results showed that most participants did not understand the difference between bacterial and viral infections before the activity began, and they continued to use antibiotics without a doctor's prescription. After the activity, participants indicated they had a better understanding of their actions and their impacts and were more engaged in the discussion sessions. The results of this activity demonstrate that outreach activities play a crucial role in increasing public knowledge about antibiotics. Outreach can also be a promotional method to prevent antibiotic resistance at the community level.